Persistent hyperparathyroidism secondary to ectopic parathyroid adenoma in lung: Case report - Valizadeh, Majid; Ebadinejad, Amir; Amouzegar, Atieh; Zakeri, Anahita (Frontiers in Endocrinology, 2022)
Primary hyperparathyroidism (PHPT) is the most prevalent cause of hypercalcemia, affecting 0.3% of the population. The only curative procedure is parathyroidectomy. Persistent PHPT occurs in 4.7 percent of patients, even in the most skilled hands. Ectopic adenomas are challenging to localize before and during surgery and frequently result in persistent PHPT. We presented a case with persistent PHPT due to lung parathyroid adenoma that was successfully resected with video-assisted thoracoscopic surgery. A 55-year-old female patient was admitted to our endocrinology clinic with persistent PHPT after four neck explorations over 16 years. The last 99m Tc-MIBI scintigraphy with SPECT showed nothing suggestive of parathyroid adenoma, neither in the neck nor the mediastinum, but a solitary nodule as an incidental finding was reported in the lower lobe of the right lung, which was highly probable for a parathyroid adenoma in a fluorodeoxyglucose PET scan. Pathological examination ruled out parathyromatosis and lung malignancy; despite its location outside the anticipated embryonic pathway, pathology revealed the presence of an ectopic parathyroid adenoma. After the surgery, serum parathyroid hormone and calcium levels decreased, and hypoparathyroidism was corrected with calcium carbonate and calcitriol.